School staff`s perceptions of managerial and technological barriers to mainstreaming special needs students - Mohannad althawabeyeh, Enas Abulibdeh, Hytham M Bany Issa, Zuhrieh Shana, (Opción, 2020)
This study aims to identify the perceived managerial barriers of principals, teachers and pre-service teachers on mainstreaming special needs students in the United Arab Emirates schools. Through using qualitative research methodology, the data was collected adopting open-ended questionnaires and conducting interviews with school principals, teachers and pre-service teachers. Initial results revealed that the perceptions of the main parties of the barriers are multidimensional. In conclusion, special education experts should select technologies, programs, tools and equipment that best support the curriculum and educational performance of special needs students.